Case report and review of the literature: Successful transition from acute continuous veno-venous hemodiafiltration therapy to chronic peritoneal dialysis in a chronically ventilated child with hypoplastic left heart syndrome following fontan - Martin, Susan D.; Lande, Marc B.; Kuebler, Joseph D.; Cholette, Jill M. (Frontiers in Pediatrics, 2022)
The physiology of total cavopulmonary connection following Fontan palliation depends on low pulmonary vascular resistance (PVR) in order to maintain pulmonary blood flow (PBF) and adequate oxygenation, and results in higher central venous pressures and limited renal perfusion pressure and cardiac output. Positive pressure ventilation with mechanical ventilation increases intrathoracic pressure and raises central venous pressure (CVP) and can further limit pulmonary and renal perfusion. Fluid removal with intermittent hemodialysis (HD) can be challenging in Fontan patients and cause intolerable hypotension, however the increased abdominal filling pressures during peritoneal dialysis (PD) dwells can exacerbate systemic venous hypertension seen in Fontan patients and threaten adequate PBF and cardiac output. Successful transition to PD in a chronically ventilated patient with hypoplastic left heart syndrome (HLHS), end-stage renal disease (ESRD) and Fontan physiology has not been described. We present details outlining the successful transition across multiple modalities of renal replacement therapy to assist other teams faced with similar challenges in chronically ventilated Fontan patients with ESRD.